THE ROLE OF JOB CHARACTERISTICS ON JOB SATISFACTION OF CREATIVITY INDUSTRY EMPLOYEES - Brahmana, Sunardi Sembiring; Simanjuntak, Herbert Irfan; Supyko, Try; Saudi, Mohd Haizam (CENTRAL ASIA AND THE CAUCASUS, 2022)
Creative industry is tied to creative performance of employees. This performance of creative employees relied greatly on their perception to their job. This study was designed to investigate the relationship of job characteristics and job satisfaction of employees on creative industry particularly in Bandung city. Data were collected from114 creative employees engaging in design, advertising, architecture, and fashion business within creative industry of Bandung city. This study found out that job characteristics and its five dimensions positively and significantly affected job satisfaction of employees in creative industry in Bandung city. In case of result implications of this study, management of the companies within creative industry in Bandung city requires to understand and model a job with characteristics perceived interesting and challenging by creative employees.